PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERATING - Ardila, Isna; Fadhila, Novi (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2017)
Corporate Social Responsibility (CSR) is a form of corporate social responsibility to all stakeholders namely consumers, employees, shareholders, community and environment in all aspect of company operations. Disclosure of Corporate Social Responsibility focusess on three indicators, namely economic, social and environment. The objectives to be achieved from this research are The Economis of CSR, The Social of CSR and The Environment of CSR which have an effect on Profitability with Good Corporate Governance as a moderating variable. This research was conducted at consumer goods industry companies listed in Indonesia Stock Exchange year 2014 â 2016. Researches used company as sample which was taken by using purposive sampling method as of the total sample was 60. Sources of data used are secondary data in the form of financial statements and annual reports of companies. Analysis of Hypothesis testing was by using multiple regression. The result showed that The Economic of CSR, Social and Environment simultaneously have no effect on Profitability. The Economics of CSR has no effect on Profitability partially, The Social of CSR has no effect on Profitability, and The Environment of CSR has a significant effect on Profitability. Good Corporate Governance does not moderate Corporate Social Responsibility toward Profitability.Keywords: corporate social responsibility, profitability, good corporate governance